MEDIA PEMBELAJARAN FLIPBOOK DIGITAL BERBANTUAN APLIKASI CANVA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Eka Syahfitri; Bunga Mulyahati; Maisarah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Reading comprehension skills for students play an important role as the main foundation in the student learning process in all subjects. Based on initial observations in grade V of SDN 2 Meurandeh, it was found that 16 out of 21 students (76.20%) had low reading comprehension skills. Therefore, this study aims to develop digital flipbook learning media assisted by the Canva application to improve the reading comprehension skills of grade V elementary school students. This type of research is Research and Development with the ADDIE development model. The subjects of this study were 21 students and a teacher of SDN 2 Meurandeh. This study was located at SDN 2 Meurandeh, Langsa City, Aceh Province. This study used research instruments in the form of observation sheets, interview sheets, validation sheets, practicality sheets, and test sheets. Data were analyzed using quantitative and qualitative data analysis techniques. The results of the study indicate that digital flipbook media is very feasible and very practical to apply in learning. Digital flipbook media has also proven effective in improving students' reading comprehension skills, this can be seen from the posttest results of 100% which is very effective. Based on the research results, the application of digital flipbooks is highly recommended to improve reading comprehension skills at the elementary school level.